A regional initiative to improve cleaning of high-touch surfaces in long-term care facilities. (14th July 2020) - Calfee, David P.; O'Neil, Robert P.; Sylvester, Quin; Bosk, Jared M.; Sumer King, Zeynep; Langguth, Karyn; Lutterloh, Emily C.; Blog, Debra
Abstract: A total of 38 long-term care facilities within a region participated in a 3-month quality improvement initiative focused on environmental cleaning and disinfection. Significant improvements in daily and discharge cleaning were observed during the project period. Further study of the sustainability and clinical impact of this type of initiative is warranted.